Always on the tipping point – A search for signals of past societies and related peatland ecosystem critical transitions during the last 6500 years in N Poland. (1st December 2019) - Lamentowicz, M.; Kołaczek, P.; Mauquoy, D.; Kittel, P.; Łokas, E.; Słowiński, M.; Jassey, V.E.J.; Niedziółka, K.; Kajukało-Drygalska, K.; Marcisz, K.
Abstract: We explored past critical transitions in a peatland located in N Poland using a densely dated ( × 44 14 C dates and ×26 210 Pb), high-resolution multi-proxy profile. A 6500-year record was supported by a very robust age-depth model. Changes in land use, climate and carbon sequestration in northern Poland were investigated using a range of biotic proxies. We determined critical transitions in the development of the mire which were dependent upon extrinsic drivers. The trophic status of the mire shifted several times during the last 6.5 millennia. The pattern of changes suggests that it was very sensitive to different changes in the peatland basin. We identified several factors which may have driven transitions between the bog and fen state as a response to catchment hydrology changes largely driven by human impact which overlapped with periods of climate change. We determined the vegetation threshold in relation to microcharcoal which could be related to fire intensity. Based upon microcharcoal and pollen analyses, the local plant community threshold for fire intensity was estimated to be ca 7500 microcharcoal particles/cm 2 /year. We discovered that this level was also an important tipping point for the divergence between plants positively (e.g. human indicators and Carpinus betulus ) or negatively related (e.g. Quercus ) related to fires. This local threshold was related to ecological changes related to the emergence and fall of subsequent human communities. The first pollen grains indicating human activities in the deposits are dated to ca. 6000 cal. BP. The strongest signal comes from the Neolithic, the Bronze Age, the Pre-Roman Period and the Roman Period. These past societies exploited natural resources and deforested the landscape while actively using fire. We inferred a distinct human influence since ca. 5000 cal. BP (the Neolithic) until the Early Middle Ages with strong evidence during the Bronze Age and Roman Period which demonstrates the high importance of the area until the transition from the tribe period to the Polish state. The peatland possibly recorded several climatic shifts, however the climate change signals were modified by human impacts which actively changed the environmental conditions. Highlights: We explored densely dated (44 14 C & 210 Pb dates) multi-proxy peat profile from N Poland. We determined critical transitions in the peatland development in the last 6.5 kyrs. We determined quantitative fire peak analysis of the charcoal data. We estimated local fire threshold in relation to pollen-based vegetation reconstruction. We recorded remarkably strong human impact during the Bronze Age and Roman Period.